2022
DOI: 10.3390/buildings12122132
|View full text |Cite
|
Sign up to set email alerts
|

The Evolution, Hotspots, and Trends in Research on Facilities of Combined Medical and Nursing Care for the Elderly

Abstract: With the significant increase in global ageing and its derivative risks, governments and academic communities have been widely concerned with research on facilities of combined medical and nursing care for the elderly (FCMNCE). Using Citespace and VOSviewer bibliometric software, in this paper, we explore the evolutionary phases, hotspots, and trends in research on FCMNCE. First, the concept and connotation of FCMNCE are clarified. Secondly, based on a bibliometric analysis of the number of annual publications… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 75 publications
0
3
0
Order By: Relevance
“…Through the study, we found that the living environment and daily behaviors of this particular group of the elderly in traditional Miao dwellings in western Hunan are very different from those in urban residences and nursing homes, which leads to different physical and psychological needs, and thus affects their respective health [39][40][41][42][43][44][45]. However, the health of the elderly has been recognized as an important and urgent issue.…”
Section: Discussionmentioning
confidence: 99%
“…Through the study, we found that the living environment and daily behaviors of this particular group of the elderly in traditional Miao dwellings in western Hunan are very different from those in urban residences and nursing homes, which leads to different physical and psychological needs, and thus affects their respective health [39][40][41][42][43][44][45]. However, the health of the elderly has been recognized as an important and urgent issue.…”
Section: Discussionmentioning
confidence: 99%
“…The analysis of keyword clusters can condense the co-occurrence network of RFCMRS keywords into a relatively small number of research clusters, aiding in the identification of key issues within a specific research domain [45,91]. Based on the keyword clustering analysis, RFCMRS can be categorized into 10 main clusters, as shown in Figure 12 and Table 8.…”
Section: Analysis Of Keyword Clustersmentioning
confidence: 99%
“…Keyword cluster analysis can enhance the conciseness of the co-occurrence network of RFCRS keywords, condensing a substantial number of linked keywords into a relatively minor set of clustered research issues. It aids in identifying pivotal issues within a particular field of study [58,59]. In this process, CiteSpace employs the log-likelihood ratio algorithm to label each research topic cluster.…”
Section: Collaborating Nationsmentioning
confidence: 99%